(untitled) (Journal of Oriental Studies, 2016)
the article describes the difficulties of translation diplomatic terminologyof chinese language and given their species. Features of representing the difficulties of translation are: linguistic specific, national color, historicism, the differences between the grammatical structure of languages, the equivalence and the adequacy of the translation.